Advances in teaching physical chemistry - Ellison, Mark D. (American Chemical Society, 2008)
This book brings together the latest perspectives and ideas on teaching modern physical chemistry. It includes perspectives from experienced and well-known physical chemists, a thorough review of the education literature pertaining to physical chemistry, a thorough review of advances in undergraduate laboratory experiments from the past decade, in-depth descriptions of using computers to aid student learning, and innovative ideas for teaching the fundamentals of physical chemistry. This book will provide valuable insight and information to all teachers of physical chemistry